Antimicrobial Susceptibility Pattern of Selected Bacterial Pathogens Isolated from High Vaginal Swab - Syed Zahoor Ul Hassan Zaidi, Arshad Mahmood, Syed Muhammad Qasim Khan, Malook Khan, Kiran Irshad, Roohul Islam, Muhammad Junaid Irshad Awan, Syed Saoud Zaidi, Uroosa Naseem, Asmat Ullah Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
The study determines the prevalence and resistance among pathogenic bacteria against used antibiotics. The isolates were identified biochemically and subjected to antibiotic sensitivity using disk-diffusion method. A total of 210 bacterial isolates were tested, 175 (83.3%) were reported positive whereas 35 (16.6%) were found negative for HVS. The isolates were initially identified on colonies morphology and later via biochemical tests. The gram positive bacteria isolates i,e Staphylococcus aureus was found 48 (23.3%), followed by lactobacillus and least value belonged to Staphylococcus epidermidis i.e, 7 (3.3%). While gram negative bacteria Escherichia coli were 56 (26.6%), followed by Pseudomonas aeruginosa 36 (17.14%) and least value was of Proteus vulgaris. i.e, 7 (3.3%). All the isolates were subjected to antibiotics susceptibility testing. At least six antibiotics were shown to be resistant in bacterial isolates. Antibiotic resistance was found in considerable abundance in the clinical isolates, according to the findings. Antibiotic susceptibility testing and surveillance are essential on a regular basis to avoid treatment failure and the emergence of antibiotic resistance.